Sustainable urban logistics: What are we talking about?. (December 2019) - Strale, Mathieu
Abstract: Sustainable urban logistics is a trendy research theme that addresses societal, environmental and industrial challenges. The purpose of this article is to examine how the academic literature investigates sustainable urban logistics by using a survey. It appears that this literature is highly biased. Technical problems, the search for optimization and solutions and the dissemination of good practices dominate the topics and methods mobilized. However, the literature pays scant attention to environmental and social issues, which are an important part of sustainable development. This gap in the literature calls for the development of a critical investigation of urban logistics.